Comparison of Clinical and Epidemiological Features of Shiga Toxin-Producing Escherichia coli O157 and Non-O157 Infections in British Columbia, 2009 to 2011 - Xuetao Wang; Marsha Taylor; Linda Hoang; Judi Ekkert; Craig Nowakowski; Jason Stone; Greg Tone; Steven Trerise; Ana Paccagnella; Titus Wong; Eleni Galanis (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Shiga toxin-producing Escherichia coli (STEC) are major foodborne agents that have the potential to cause severe enteric illnesses and large outbreaks worldwide. Several studies found non-O157 infections to be clinically milder than O157 STEC infections.